2008
DOI: 10.1370/afm.844
|View full text |Cite
|
Sign up to set email alerts
|

The Experience of Pay for Performance in English Family Practice: A Qualitative Study

Abstract: PURPOSEWe conducted an in-depth exploration of family physicians' and nurses' beliefs and concerns about changes to the family health care service as a result of the new pay-for-performance scheme in the United Kingdom (Quality and Outcomes Framework [QOF]). RESULTS Participants believed the fi nancial incentives had been suffi cient to change behavior and to achieve targets. The fi ndings suggest that it is not necessary to align targets to professional priorities and values to obtain behavior change, althoug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
188
1
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(196 citation statements)
references
References 25 publications
4
188
1
3
Order By: Relevance
“…A recent analysis of a large pay-forperformance program with family practitioners in the British National Health Service reported improved quality of care for 2 of 3 chronic conditions followed by the slowing of improvement and a reduction in continuity of care 7 as well as unintended changes in staff and practitioner-patient dynamics. 8 Overall, the aggregate evidence available is difficult to interpret because of the wide variety of interventions, target behaviors, and health care environments represented.…”
Section: Discussionmentioning
confidence: 99%
“…A recent analysis of a large pay-forperformance program with family practitioners in the British National Health Service reported improved quality of care for 2 of 3 chronic conditions followed by the slowing of improvement and a reduction in continuity of care 7 as well as unintended changes in staff and practitioner-patient dynamics. 8 Overall, the aggregate evidence available is difficult to interpret because of the wide variety of interventions, target behaviors, and health care environments represented.…”
Section: Discussionmentioning
confidence: 99%
“…148 Incentives also reinforce the office team structure. 149 Oversight is essential to the ultimate success of a patient centered medical home system of care. The United Kingdom established the National Institute for Health and Clinical Excellence to manage incentives and define objectives of their health system.…”
Section: Reimbursement Modelsmentioning
confidence: 99%
“…16 Such a process is important to prevent resentment among physicians who are unable to meet benchmarks for payment, despite hard work. 19 Conversely, other studies have found that many physicians who receive payments in a pay-for-performance system do not necessarily consciously make improvement to enhance financial performance. 20 Only 54% of eligible physicians participated in the present gainsharing program.…”
Section: Discussionmentioning
confidence: 97%